Avaliação da rebsorção óssea do periodonto de cães por meio da tomografia computadorizada - Sabino, Emanuelle Guidugli [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Dental diseases occur in over 85% of the canine population with six or more years of age (Wiggs and LOBPRISE, 1997) and they are responsible for various degrees of inflammation that can result in tooth loss and systemic disorders resulting from installed chronic inflammation (IRON et al, 2009). With this project the aim was to assess the thickness of the bone lingual boards and labial of tooth 309, in order to determine bone density in Hounsfield Units scale of the mandible, besides the periodontal bone resorption in dogs with different degrees of periodontal disease, by means of a CT as a diagnostic tool. We selected 36 Poodles, grouped in young animals, adults and senior animals, and within each group there was a range of animals with mild, moderate and severe degrees of periodontal disease. There was no presence of healthy animals in this experiment. The clinical evaluation along with the CT scan provided relevant results to the issue of involvement of periodontal disease in bone resorption site, and the animals with a high degree of periodontal disease had higher alveolar bone loss of the buccal and lingual jaw. Therfore the conclusion that was arrived at is that periodontal disease is found in 100% of animals and computed tomography provides additional means for assessing bone resorption provided by conventional skull and intraoral radiography

As doenças odontológicas ocorrem em mais de 85% da população canina com seis anos ou mais de vida (WIGGS e LOBPRISE, 1997) e é responsável por diversos graus de inflamação que podem acarretar em perda dos dentes e distúrbios sistêmicos decorrentes do processo inflamatório crônico instalado (FERRO et al, 2009). Com este projeto, objetivou-se avaliar a espessura das tábuas ósseas lingual e vestibular do dente 309, de maneira a determinar a densidade óssea na escala de Unidades Hounsfield da mandíbula, além da reabsorção óssea do periodonto em cães com diferentes graus de doença periodontal, por meio da tomografia computadorizada como ferramenta diagnóstica. Foram selecionados 36 cães da raça poodle, agrupados em jovens, adultos e idosos, sendo que cada grupo abrangiaanimais com leve, moderado e severo grau de doença periodontal. Não houve a presença de animais saudáveis neste experimento. A avaliação clínica somada ao exame tomográfico forneceram resultados relevantes na questão de envolvimento da doença periodontal na reabsorção óssea local, sendo que os animais com elevado grau de doença do periodonto apresentaram maior perda óssea alveolar nas faces vestibular e lingual de mandíbula. Com isso concluiu-se que a doença periodontal encontra-se em 100% dos animais e a tomografia computadorizada fornece meios para complementar a avaliação da reabsorção óssea fornecida pelo exame radiográfico convencional de crânio e intra-oral
Keywords: Doenças periodontais; Cão - Doenças; Odontologia veterinaria; Diagnóstico por imagem; Mandíbula; Periodontal diseases